Centralized Data Governance: The Key to Digital Transformation and Improving Accountability at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province - Arisal (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This article analyzes data governance issues at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province, resulting in slow public services and complex bureaucracy. Various structural and technical issues, such as the lack of information system integration that creates the phenomenon of "information silos," and reliance on manual processes, collectively hamper digital transformation and accountability. This paper uses a qualitative method with a literature review approach. Data were collected from various secondary sources, including scientific journals, official government reports, management books, and laws and regulations related to the Electronic-Based Government System (SPBE) and public services. Seven policy alternatives are formulated to address these issues, ranging from directive approaches to fundamental changes. These policy alternatives include the formation of a special task force, standardization of data formats, mandatory use of a centralized system, priority budget allocation for technology, the formation of a helpdesk team and ongoing training, gradual data integration, and business process reengineering (BPR). Conceptual and theoretical support, such as Data Governance Theory, the Concept of Digital Transformation, the Concept of Accountability, and the Concept of Public Sector Innovation, provide a strong scientific foundation for each recommendation. It is hoped that this policy can be a strategic guide for the Regional Office of the Ministry of Religion of West Sulawesi Province to create an efficient, transparent and modern bureaucracy, which will ultimately improve the quality of service to the community.